2016
DOI: 10.1108/ijpsm-08-2015-0155
|View full text |Cite
|
Sign up to set email alerts
|

Organizational underpinnings of interactive decision making: an empirical inquiry

Abstract: Purpose – Interactive decision making has become a recurrent practice across countries, policy sectors and tiers of government. The purpose of this paper is to analyze how organizational arrangements, i.e. the way the interactive process is designed, influence its outcomes. Design/methodology/approach – The research is carried out through a multiple case study. Four cases of interactive decision making are analyzed using a qualitative fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
(76 reference statements)
1
9
0
Order By: Relevance
“…The study results show that the organisational antecedents of structure and culture explain a significant amount of variation in the EO dimensions of innovativeness, risk taking and proactiveness. In terms of H1 , our study findings resonate with prior studies where a positive relationship between organisational structure and EO has been reported (Fedele et al , 2016). Middle-level managers who operate in an organic/flat structure display higher levels of EO.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The study results show that the organisational antecedents of structure and culture explain a significant amount of variation in the EO dimensions of innovativeness, risk taking and proactiveness. In terms of H1 , our study findings resonate with prior studies where a positive relationship between organisational structure and EO has been reported (Fedele et al , 2016). Middle-level managers who operate in an organic/flat structure display higher levels of EO.…”
Section: Discussionsupporting
confidence: 90%
“…However, a range of organisational factors such as structure, culture and incentive systems, often stifle proactiveness by public sector managers. Furthermore, public agencies have a variety of stakeholders, each of whom place separate demands and constraints on managers that affect their proactiveness (Fedele et al , 2016).…”
Section: Entrepreneurship and The Public Sector Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…This element can be of interest for practice since it concerns the design of organizational arrangements for coproduction. Organizational design, in fact, is central in shaping decisions and behaviors (Egeberg, 2003) and many contributions on stakeholder engagement have looked at organizational arrangements (in this case the “width” of participation) as the antecedents of its effects (Edelenbos and Klijn, 2005; Fung, 2006; Fedele et al , 2016).…”
Section: Insights Critiques and Future Researchmentioning
confidence: 99%
“…Second, the research design accounts for influencing factors of participation processes to enable inferential generalizability of findings. By keeping context (Nabatchi and Amsler, 2014) and policy sector homogeneous (Fedele et al , 2016), the study’s findings on role patterns, role exercise and effectiveness can build the ground for future research on citizen participation and public leadership.…”
Section: Introduction and Research Objectivementioning
confidence: 99%